2019
DOI: 10.1016/j.cub.2019.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Three Genes Define a Bacterial-Like Arsenic Tolerance Mechanism in the Arsenic Hyperaccumulating Fern Pteris vittata

Abstract: Arsenic is a carcinogenic contaminant of water and food and a growing threat to human health in many regions of the world. This study focuses on the fern Pteris vittata (Pteridaceae), which is extraordinary in its ability to tolerate and hyperaccumulate very high levels of arsenic that would kill any other plant or animal outside the Pteridaceae. Here, we use RNA-seq to identify three genes (GLYCERALDEHYDE 3-PHOSPHATE DEHYDROGENASE (PvGAPC1), ORGANIC CATION TRANSPORTER 4 (PvOCT4), and GLUTATHIONE S-TRANSFERASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…During the literature search on PV it was found that using RNAi-based gene silencing, other authors demonstrated critical roles for three genes in establishing arsenate tolerance in PV which were PV GAPC1 (Glyceraldehyde 3-Phosphate Dehydrogenase), PV OCT 4 (Organic Cation Transporter 4) and PvGSTF1 Glutathione S-Transferase) [40].…”
Section: Discussionmentioning
confidence: 99%
“…During the literature search on PV it was found that using RNAi-based gene silencing, other authors demonstrated critical roles for three genes in establishing arsenate tolerance in PV which were PV GAPC1 (Glyceraldehyde 3-Phosphate Dehydrogenase), PV OCT 4 (Organic Cation Transporter 4) and PvGSTF1 Glutathione S-Transferase) [40].…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 ] Similarly, the GAPC1, GSTF1 , and OCT4 proteins are required for the import and reduction of arsenate inside the cells. [ 65 ] However, the uptake pathway of arsenite in Pteridaceae ferns has not been fully elucidated, partly due to the difficulty in generating transgenic ferns. [ 66 ] In rice, the uptake of arsenite into rice roots is primarily facilitated by OsNIP2;1 ( Ls1 ), a member of the nodulin‐26 like intrinsic proteins (NIPs) that is also responsible for the uptake of silicon (Si).…”
Section: Figurementioning
confidence: 99%
“…The expression of PvACR3;1 from P. vittata in A. thaliana and tobacco ( Nicotiana tabacum ) was shown to increase As retention in the roots, thereby decreasing As accumulation in the shoots [205]. Recent gene expression studies revealed a close cooperation of different uptake and storage mechanisms responsible for As hyperaccumulation and hypertolerance in the gametophytes of P. vittata [206]. Based on a similar mechanism previously established for As tolerance in Pseudomonas aeruginosa [207], Cai et al, [206] proposed the following model for As hyperaccumulation and tolerance in P. vittata : As(III) crosses the plasma membrane by the aquaporin AsTIP4 and is transported through the tonoplast for vacuolar storage by PvACR3.…”
Section: Polyvalent Elements With a Stable +3-oxidation State: Iromentioning
confidence: 99%